Pengaruh Strategi, Segmenting, Targeting, Dan Positioning Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Ayam Goreng Nelongso Di Kota Malang) - Fahruddin Angga Pradana; M Hufron; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research aims to analyze how the influence of segmenting, targeting and positioning strategies on purchasing decisions in the Ayam goreng Nelongso in Malang city simultaneously and partially. This research is a quantitative study using Explanatory Research techniques with a sample of 90 respondents and use non probability sampling technique with a purposive sampling method. The data source used in this study uses primary data sources with the method of data collection using a questionnaire. The analysis technique used multiple linear regression analysis and using SPSS Software for windows to analyze hypothesis testing. The conclusions of this study are (1) Segmenting, Targeting, and Positioning simultaneously have a significant effect on Purchasing Decisions. (2) Segmenting, partially, does not significantly influence Purchasing Decisions. (3) Targeting and Positioning partially have significant influence on Purchasing Decisions. Keywords: Segmenting, Targeting, positioning, Purchasing decisions.